An introduction to international marketing a guide to going global - Lewis, Keith 1940-; Housden, Matthew (Page, 1998)
This jargon-free introduction de-mystifies the language of international marketing, providing a guide that is both accessible and essentially practical in nature. You will find advice on how to market products and services internationally, and demonstrations in the form of case studies to show how these devices can work in the real world. The book is written in an authoritative and easily accessible way and will be useful to marketing practitioners and students (CAM, CIM) alike.
Literaturverz. S. [177] - 180
Keywords: Export marketing; Produktpolitik; Internationales Marketing; Internationales Management